Просторовий розподіл голих амеб у донному ґрунті стоячої водойми поблизу м. Дніпро (Україна) - Пацюк, Марина; Patsyuk, Maryna (Східноєвропейський національний університет імені Лесі Українки, 2017)
Проаналізовано особливості просторового розподілу голих амеб у донному ґрунті стоячої водойми поблизу м. Дніпро. Усього в різних шарах донного ґрунту ідентифіковано дев’ять видів амеб та сім морфотипів. Загальна закономірність проявляється в зменшенні видового різноманіття амеб і їх морфотипів зі збільшенням глибини донного ґрунту досліджуваної водойми. Due to the lack of data on the ecology of naked amoebae, we have studied the spatial distribution of naked amoebae in the bottom soils of a small standing water body near the Dnieper. Totally, nine species of naked amoebae and seven morphotypes are distinguished in the different layers of bottom soil. Changes in the species structure of amoebae and their morphotypes are analyzed in depth. There were marked species S. stenopodia, R. platypodia, Ripella sp. in the majority of samples. The Hartmannella sp. turned out to be small. The upper soil layers of the investigated reservoir characterize the greatest variety of amoeba species and their morphotypes. Amoebas of the fan-shaped morphotype occupy all the bottom soil layers. Groups of amoebae are distinguished according to the size features (large, medium and small) and two ecological groups of amoebae based on their distribution in the bottom soils of reservoirs.
Spatial Distribution of the Naked Amoebae in the Bottom soil of Standing Water Body Near the Dnieper (Ukraine).
Keywords: голі амеби; донні ґрунти водойм; морфотипи; naked amoebae; bottom soils of reservoirs; morphotypes; protists